Kepatuhan Wajib Pajak Penyedia Platform Marketplace E-Commerce Sebagai Pemungut Pajak Pertambahan Nilai Perdagangan Melalui Sistem Elektronik - Mustika Prabaningrum Kusumawati; Ahmad Khairun Hamrany; Ari Nur Rahman (Universitas Muhammadiyah Purwokerto, 2021)
The development of digital technology in the industrial era 4.0 distorts tax cuts and collections in the e-commerce marketplace. This study provides an overview of conditions in the field of compliance and voluntary intentions of e-commerce marketplace platform providers and individuals and / or entities to register as PPN PMSE taxpayers and tax collectors. In addition, it can also find out a review of the juridical aspects of the applicable regulations if the taxpayer provides the domestic e-commerce marketplace platform application if it is determined as a PMSE VAT Collector. The method used is qualitative research using an ethnographic approach which is considered appropriate for social science research based on questionnaire data, interviews and other documentary data. The level of compliance of companies providing the e-commerce marketplace platform is divided 1) the level of compliance based on deductions, deposits and reporting related to corporate tax itself where there is an attempt to comply as a form of obligation of the taxpayer. 2) the level of compliance based on the voluntary intention to register to be appointed as a PPN PMSE collector, which is still very low. In the juridical aspect, it is only found that the additional obligation lies in the collection of PPN PMSE on intangible Taxable Goods or Taxable Services from outside the Customs area whose transactions are carried out within the Customs area.Keywords: Compliance; e-commerce marketplace; PPN; PMSE; Taxpayer